PENGARUH CARA BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR BIOLOGI SISWA KELAS II SMUN COLOMADU KARANGANYAR - MUZAYYINAH MUZAYYINAH; MARIDI MARIDI; WIRADI WIRADI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2005)
This research were aimed to know the impact of highly motivated in biological learning and learning method toward the student’s achievement. This is the descriptive quantitative ex post facto research.. The population being sampled was all student of second grade of SMU N Colomadu, Karanganyar, which comes from 79 students of two classes. Clustered random sampling was used. The research variable were learning method and learning motivation as the independent variable, beside the achievement as a dependent one. The data was collected by collecting technique which using documentation and questionnaire. The data was then analysed by analysis of variance and linear regression.Research results are: (1) there is an impact of learning method on the student achievement. (2) There is a significant impact of highly motivated in learning toward student achievement. (3) Both, the two factors are influence the student achievement respectively